Comparative assessment of structural indicators of Ukraine industry and the European Union - Ishchuk, Svitlana (Współczesne Problemy Zarządzania, 2018)
A comparative analysis of the structural advantages of the industry of Ukraine and the EU member states in terms of the share of industry in: output of the economy, gross value added of the economy, exports of airborne vehicles, as well as the efficiency indicator (the share of airborne emissions in the industry). The place of Ukraine among EU member states is determined on the set of relative and absolute indicators of functioning of the industrial sector of the economy. A detailed comparative estimation of the structure of the airborne assets of the industry of Ukraine and Poland was conducted.